Investigating the environmental awareness level of secondary school students: Effects of race, school type, and location - Azizah, Endut; Rahimah, Embong; Auwalu, Rabiu Ali (2017)
Environmental education is considered as a life-long process starting from pre-school level continuing through all stages of formal and informal education. Student’s environmental awareness as one of the components of environmental education has been investigated for many years in Nigeria. Due to lack of sufficient literature, this paper is aimed to investigate the level of environmental awareness and also ascertain the effects of race, type of school, and location on environmental awareness level of secondary school students in Kano State, Nigeria. It was done by conducting a survey study method. A total of 1200 respondents were selected out of 507,061 secondary school students who were in SS 2 in Kano State using simple random sampling techniques. Environmental Awareness Test was used as the instrument for data collection. The data collected were analysed using descriptive and inferential statistics. Mean and Standard Deviation was used to answer the research question while one-way ANOVA was used to test the hypotheses. The results show that the secondary school students in Kano have low environmental awareness level. It was further revealed that significant differences exist in the environmental awareness level of students for all the three levels of independent variables.